Pengaruh Orientasi Kewirausahaan, Orientasi Pasar, dan Manajemen Kualitas Total Terhadap Kinerja UMKM di Kabupaten Karanganyar - Lindungi Semesta Aji; Harini Harini; Aniek Hindrayani (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to determine the effect of entrepreneurial orientation, market orientation, and total quality management on the performance of SMEs. The research method used is descriptive quantitative with purposive sampling technique and a sample of 187 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. This study uses data analysis techniques using multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between entrepreneurial orientation on MSME performance, market orientation has a positive and significant effect on MSME performance, total quality management has a positive and significant effect on MSME performance, as well as entrepreneurial orientation, market orientation, and total quality management as a whole. simultaneously has a positive and significant effect on the performance of SMEs.